Pemberdayaan Perempuan Melalui Pendirian Kelompok Usaha Serai Pitay Berbasis Socialpreneur Guna Meningkatkan Kesejahteraan Masyarakat Kupang NTT - Arian Agung Prasetiyawan (UIN Raden Mas Said Surakarta, 2020)
KKN Nusantara 3T (Disadvantaged, Foremost, and Outermost) is the implementation of the Collective Labor Agreement between the Directorate General of Islamic Education of the Ministry of Religion and the Directorate General of Disadvantaged Areas of the Ministry of Villages Development of Disadvantaged Areas and Transmigration concerning Collaboration in the Development of a Higher Education Model Building a Village through Community Service which is signed August 7, 2019. The location of the implementation of the Community Service Program is classified into 2 Zones: the East Nusa Tenggara Province Zone with the theme